Penyuluhan Penanganan Kedaruratan Gigi dan Mulut Terhadap Anak Usia Sekolah pada Orang Tua dan Guru SDI Al-Ikhlas Cipete - Jakarta Selatan - Wirahadikusumah, Andy; Teguh, Sharren; Juliani Hardja Buntara, Magdalena; Sandra, Ferry; Cloudya Panjaitan, Caesary (JURNAL ABDIMAS KESEHATAN TERPADU, 2023)
Dental emergency is associated with immediate measures that are carried out with the aim to alleviate pain. Dental trauma is one of dental emergencies, which is injury to the teeth and or the supporting tissues of the teeth. Dental injuries are often experienced by school-aged children, in which the majority of traumatic dental injuries occur at home or school, hence it is hoped that parents and school teachers can provide appropriate treatment when dental emergencies occur in children. This community service counseling aims to increase knowledge and skills in the management of dental emergencies. Counseling was carried out by the Trisakti University Faculty of Dentistry Team to parents and teachers of Al-Ikhlas Islamic Elementary School, Cipete, Jakarta Selatan on March 11, 2023. Counseling includes learning materials regarding the management of dental emergencies and dental health education through powerpoint presentation, video, and live demonstration. Final questionnaire shows an increase in knowledge and understanding regarding the management of dental emergencies. Therefore, it can be concluded that after the counseling activity, there is an increase in the level of knowledge among parents and teachers of Al-Ikhlas Islamic Elementary School regarding the management of dental emergencies. Further training is needed to improve the ability to handle dental emergencies better.